Training on Management of Choking on Palang Merah Remaja in Middle School 1 Genteng - Rizki Yulia Purwitaningtya; Firdawsyi Nuzula; Siswoto Hadi Prayitno (Warta Pengabdian, 2019)
The Youth Red Cross (Palang Merah Remaja (PMR)) is a forum for fostering and developing Indonesian Red Cross (Palang Merah Indonesia (PMI)) youth members, PMR is one of PMI's strengths in carrying out humanitarian activities in the health sector. Various health problems that may occur anywhere and anytime that have fatal consequences such as choking can cause respiratory system disorders that can lead to death. The purpose of this activity is to increase the knowledge and management of PMR members in choking management. The method of this activity is to collaborate with the teacher of the Genteng 1 Public Middle School in informing the holding of Community Service about education and training in the management of choking, then follow-up to the principal of the Genteng 1 Public Middle School. Dissemination to students involved in training events. Training for students who are accompanied by PMR advisors about education and training in the management of choking. To support the success of this event, students were allowed to practice directly to the panthom and friends. The results of this activity showed an increase in knowledge about the management of 75% of choking with high expertise and increased ability (practice) in the control of 85% of choking with top practice ability. With this training, it is expected that all schools, especially PMR, will be able to carry out optimal handling of choking.